Modelling Potential Crop Growth Processes : Textbook with Exercises - Goudriaan, Jan (Current issues in production ecology ;, 1994)
This textbook contains the material for a course in the major principles of modelling crop growth processes. There is much more to crop growth than what is discussed in this textbook, but it provides a sound basis for further work and study in this field. Chapter by chapter the book leads the reader to different modelled aspects of crop growth, and at the end, the reader will have a good understanding of the Wageningen simulation model SUCROS for the potential production situation. By then, it will be much easier to find one's way through descriptions and listings of other models. Throughout the text, the study of the different topics is facilitated by exercises that support the course in a hands-on computer practical exercise. A very simple crop growth model, almost entirely based on radiation interception, is given first. This skeleton model is then expanded by submodels for respiration, carbon assimilation, plant development, and a more detailed model for radiation interception and reflection. Modelling of transpiration and the leaf energy balance is given by way of introduction. There are many listings of the submodels, written in the simulation language FST (FORTRAN Simulation Translator), as well as of SUCROS itself, together with plentiful comments. Some supporting theory is provided in the form of Appendices. The book is meant for students and scientists who would like to acquire a working knowledge of the technique of crop growth modelling.